The reliability analysis of isokinetic measurement of Isomed 2000 Dynamometer - Hu, S.-Q.; Mi, Y.-X.; Jiang, Y.-F. (China Sport Science and Technology, 2014)
The purpose of this study was to evaluate the reliability of Isomed 2000 dynamometer.We compared the dynamometer and different weight of barbells on torque.Nineteen normal subjects(15male,4female)ages 24.1±5.6with no history of related injury were tested unilaterally for concentric extension/flexion,back at 60°/s,hip at 60°/s,180°/s and 240°/s,knee at 60°/s and 240°/s,ankle at 60°/s,180°/s and 240°/s,shoulder at 60°/s and 180°/s,elbow at 60°/s,180°/s and 240°/s,wrist at 60°/s and 240°/s,utilizing standard Isomed2000 protocol.Each subject was tested two times with an interval of 4~7days.Statistical analysis of data showed that 1)The correlation coefficient(r)between the torque measured and calculated was>0.999.2)the isokinetic concentric extension/flexion mode for back at 60°/s,hip at 60°/s and 180°/s,knee at 60°/s and 240°/s,ankle at 60°/s and 180°/s,shoulder at60°/s and 180°/s,elbow at 60°/s and 180°/s,wrist at 60°/s and 240°/s of the Isomed 2000 dynamometer was with test-retest reliability ranging from 0.71 to 0.98.3)The intraclass correlation coefficient(ICC)of elbow extension/flexion peak torque and average peak torque at240°/s to be from 0.67 to 0.82,ICC of hip flexion every parameters at 240°/s to be from0.64 to 0.83,ICC of ankle extension(dorsiflexion)every parameters at 240°/s to be from0.36 to 0.82.Conclusions:1)The measurement error of the dynamometer is small and the accuracy is fine.2)The isokinetic concentric extension/flexion mode for hip,elbow and ankle at240°/s of the dynamometer was less or not reliable for test-retest measures of peak torque,work and power;3)Other measures implied good to excellent reliable